Assessing Hydrograph Similarity and Rare Runoff Dynamics by Cross Recurrence Plots. Issue 6 (7th June 2019) - Wendi, Dadiyorto; Merz, Bruno; Marwan, Norbert
Abstract: This paper introduces a novel measure to assess similarity between event hydrographs. It is based on cross recurrence plots (CRP) and recurrence quantification analysis (RQA), which have recently gained attention in a range of disciplines when dealing with complex systems. The method attempts to quantify the event runoff dynamics and is based on the time delay embedded phase space representation of discharge hydrographs. A phase space trajectory is reconstructed from the event hydrograph, and pairs of hydrographs are compared to each other based on the distance of their phase space trajectories. Time delay embedding allows considering the multidimensional relationships between different points in time within the event. Hence, the temporal succession of discharge values is taken into account, such as the impact of the initial conditions on the runoff event. We provide an introduction to cross recurrence plots and discuss their parameterization. An application example based on flood time series demonstrates how the method can be used to measure the similarity or dissimilarity of events, and how it can be used to detect events with rare runoff dynamics. It is argued that this methods provides a more comprehensive approach to quantify hydrograph similarity compared to conventional hydrological signatures. Key Points: This manuscript presents the first application of recurrence plots in catchment hydrology CRP is used as a novel method for quantifying comprehensive hydrograph similarity based on runoff dynamics Time delay embedded phase space trajectory allows to consider relationships between magnitudes of different point in time